Peran Transformasi Digital E-Commerce untuk Mendorong Green Entrepreneurship UMKM Kuliner - Lina Isnaini; Elisabet Rahmani; Dewi Kusuma; Mintasi Indriayu (Universitas Madura, 2025)
This paper aims to analyze the role of e-commerce digital transformation in encouraging green entrepreneurship practices in culinary MSMEs and to identify supporting factors and barriers to the integration process. The research method used is Systematic Literature Review (SLR) of 31 Scopus-indexed articles and reputable journals from the 2020–2025 period. The analysis was conducted by examining findings related to aspects of digital transformation based one-commerce, and culinary MSMEs that are relevant to the implementation - commercein practicegreen Entrepreneurship. The study results show that digital transformation in e-commerce has a positive impact on energy efficiency, waste reduction, environmentally friendly packaging innovation, and increased competitiveness of MSMEs. Key supporting factors include government support, digital training, collaboration between business actors, and increased consumer awareness of green products. However, ongoing obstacles include the cost of technology implementation, limited digital literacy, uneven logistics infrastructure, and minimal regulation and access to green financing. This study emphasizes the importance of synergy between public policy, technological readiness, and the green orientation of business actors to accelerate adoption.e-commercewith practicegreen entreepreneushipin the culinary sector. These findings are expected to serve as a reference for the government, academics, and MSMEs in developing an inclusive and environmentally friendly digital ecosystem.